2022
DOI: 10.1177/0092055x221129635
|View full text |Cite
|
Sign up to set email alerts
|

“You Make Your Own Luck”: Building Cultural and Social Capital in a Major-Based Career Course

Abstract: This teaching note presents a required proseminar for sociology and criminology and justice studies majors. The American Sociological Association reported that about half of U.S. sociology program curriculum integrate career resources and about one-third offer a course. On a spring 2021 proseminar pilot self-assessment pretest, 18 students indicated it was important to them to get help on developing professional skills and materials. On that same pretest, most indicated that already developed materials would n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Notably, Senter (2020) prioritized a similar approach in a department-level program that focused on building sociology majors’ career readiness toolkits through a one-credit course. Research tells faculty that a key mentorship focus for all sociology undergraduates—not just first-generation students—should center on building knowledge around careers but that this does not often happen early or often enough (Virnoche 2022). In fact, the American Sociological Association (2018) conducted an overview of career-related curricula across U.S. sociology programs and found that only half of programs offered career content in their curriculum and just one-third had a required career-related course in their program.…”
Section: Background: Why Mentoring?mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Senter (2020) prioritized a similar approach in a department-level program that focused on building sociology majors’ career readiness toolkits through a one-credit course. Research tells faculty that a key mentorship focus for all sociology undergraduates—not just first-generation students—should center on building knowledge around careers but that this does not often happen early or often enough (Virnoche 2022). In fact, the American Sociological Association (2018) conducted an overview of career-related curricula across U.S. sociology programs and found that only half of programs offered career content in their curriculum and just one-third had a required career-related course in their program.…”
Section: Background: Why Mentoring?mentioning
confidence: 99%
“…Mentoring can be important to the collegiate success of first-generation students because it provides access to the unwritten norms and expectations of academia that can be pivotal in shaping academic and career outcomes (Moschetti et al 2018;Scherer 2020). However, traditional models of mentoring that focus on establishing one-on-one relationships between students and faculty often require students to know and seek out information and resources, which can heighten barriers to success for those students (Jack 2019;Scherer 2020;Virnoche 2022). Sociologists are in a unique position to address some of these inequalities given that we can draw connections between career, curriculum, and core sociological concepts like social capital (Garriott 2020).…”
mentioning
confidence: 99%
“…Tailored career development courses for Black students and professionals are significant for overcoming specific barriers and challenges that impede upon their career advancement (Virnoche, 2022). Career development courses can foster empowerment and equip Black students and professionals with the tools essential for success across a variety of career paths and industries (Salvador & Teckchandani, 2019).…”
Section: Access To Network and Opportunitiesmentioning
confidence: 99%
“…By delivering essential knowledge and skills, career development courses empower Black students and professionals, providing them with resources that are fundamental for success and advancement (Kezar et al, 2019;Lent et al, 2023). This acquired knowledge serves enables Black individuals to showcase their skills, expertise, and potential, effectively challenging and dismantling stereotypes that may impede career advancement (Edwin & Daniels, 2022;Kezar et al, 2019;Virnoche, 2022).…”
Section: Access To Network and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation